The Kinetic Model for Decolorization of Commercial Reactive Red 120 Azo Dye Aqueous Solution by the Fenton Process and Study the Effect of Inorganic Salts - Hassan, Ahmed Khudhair; AL-Rubai, Hasan Fadhil; AL-Shamary, Hadi Hassan (Al-Nahrain Journal of Science, 2018)
The degradation of a commercial azo dye Reactive Red 120 (RR120) in synthetic aqueous solution using Fenton’s oxidation has been studied. The influence of different reaction parameters such as pH, hydrogen peroxide, ferrous sulfate, and the RR 120 concentration on the oxidative degradation of RR 120 have been appraised. The optimal reaction conditions were determined and it was found to be pH = 3.50, [H2O2] = 1.1×10-3 M, [Fe2+] = 1.0×10-4 M for [RR 120] = 7.5×10-5 M. Under optimal conditions, 96.0% decolorization efficiency of dye in aqueous solution was achieved after 15 min of reaction. The effect of azo bond loading (Lazo bond), from 0.25 to 1.0, and pH values from 2.5 to 5.0 were estimated on RR 120 color removal kinetic rates. A correlation between the kinetic of the color removal rates (ln k2) versus Lazo bond was carried out at the different pH levels. The color removal rate increased linearly with decreasing Lazo bond, in the order of pH: 3.5 > 5.0 > 2.5. All the experimental data were analyzed using the first and second-order kinetic models. The second-order provides the best correlation of the data. 67% Chemical Oxygen Demand (COD) removal efficiency of the RR 120 were achieved after 15 min of reaction by fixing the initial H2O2/Fe2+ molar ratio, COD loading factor (LCOD), and pH at 11, 0.25 and 3.5, respectively. Also, the effects of various inorganic anions (such as Cl−, SO42-, CO32-, etc.) on the oxidation efficiency of Fenton were studied. This study can benefit planners who deal with contaminated textile wastewater using chemical treatment by advanced oxidation technologies.